O simbolismo da individuação no Castelo Interior - Ruston, Yvone de Rezende (2011)
The objective of this work is to offer an analogy between Teresa de Avila s book Interior Castle and the Analytic Psychology s individuation process. The symbolic method of Analytic Psychology presents itself as a resource that allows the recovery of the language and symbolism of religious experience, permitting the understanding of the individuation process, and the assimilation of personal stories in those aspects that challenge rational understanding. During research, we selected some symbolic images from Interior Castle that are analog to the individuation process. The symbolism of Interior Castle reveals itself on a journey in search of the main dwelling, the Center, and in relation to the secondary dwellings. During the journey, the symbolism of the serpents and demons represents existence conflicts. The symbolic triad: worm-cocoon-butterfly offers an analogy to understand the psychic transformation. The image of the spiritual marriage symbolizes the joining of the individual and God, and reflects the integration of the conscious and unconscious mind, a psychic dynamic proper to human development. The union with Christ as a symbol of Self is a powerful analogy to the impasses of life and can nurture the human psych with symbolism able to promote the individuation process